2017
DOI: 10.1007/s11881-017-0149-3
|View full text |Cite
|
Sign up to set email alerts
|

Length effects in pseudo-word spelling: stronger in dyslexic than in non-dyslexic students

Abstract: It is often discussed whether dyslexics show a deviant pattern of reading and spelling development when compared to typically developing students, or whether they follow the same pattern as other students, only at markedly slower rate. The present cross-sectional study investigated phonological encoding skills in dyslexic Danish students. We compared dyslexic and non-dyslexic students from grades 3, 5, 7, and 9 and examined whether effects of item length were stronger in the dyslexic groups. Mixed between-with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, in adults with acquired dysgraphia longer words elicited a higher number of spelling errors (Buchwald & Rapp, 2003;Tainturier & Caramazza, 1996). Furthermore, it was recently observed that length had an even more detrimental effect in spelling in children and adolescents with dyslexia compared to typically developing peers (Juul & Petersen, 2017). Because stimulus length can influence spelling accuracy, considering length effects in the study of spelling acquisition allows a more refined characterization of the development of each orthographic complexity.…”
Section: Length and Lexicality Effectsmentioning
confidence: 99%
“…For example, in adults with acquired dysgraphia longer words elicited a higher number of spelling errors (Buchwald & Rapp, 2003;Tainturier & Caramazza, 1996). Furthermore, it was recently observed that length had an even more detrimental effect in spelling in children and adolescents with dyslexia compared to typically developing peers (Juul & Petersen, 2017). Because stimulus length can influence spelling accuracy, considering length effects in the study of spelling acquisition allows a more refined characterization of the development of each orthographic complexity.…”
Section: Length and Lexicality Effectsmentioning
confidence: 99%
“…If, on the contrary, they present with error types commensurate with their spelling level, this would suggest an overall delay in all linguistic processes involved in spelling, commensurate with their language skills. This methodology has been used to characterize the spelling profiles of dyslexic children, pointing to subtle differences in their spelling, over and above those expected given their spelling level (e.g., specific difficulties with the silent letter e, Bourassa and Treiman, 2003; and with consonant clusters in English, Bruck and Treiman, 1990; or with long words in Danish, Juul and Petersen, 2017). If such differences could be found in children with DLD, they might be a marker of language difficulties in spelling, and a potential target for future interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of both the lexical and the sublexical spelling routes on handwriting speed was assessed by manipulating, respectively, the lexicality (words, pseudowords) and the length of stimuli included in a spelling-to-dictation task. Although these variables are known to affect spelling processes (Henry, Beeson, Stark, & Rapcsak, 2007;Juul & Petersen, 2017), evidence for their influence on kinematic measures of handwriting is more reduced than that obtained for other psycholinguistic variables such as word frequency or phonology-toorthography regularity. Based on previous evidence suggesting that sublexical variables affect handwriting movements more consistently than lexical variables (Afonso et al, 2018), we expect to find significant effects of word length on handwriting speed in this task, but it is less clear if lexicality will affect writing durations.…”
Section: The Present Studymentioning
confidence: 96%